Study of thermoelectric power generator under transient and steady state conditions - Kew, Guan Yuan (2017)
The thermoelectric effect is first discovered in the early 19th Century by Thomas Johann Seebeck and Jean Athanase Peltier. The thermoelectric generators had low commercial value due to its low thermoelectric conversion efficiency and figure of merit. The research on thermoelectric generators gained traction in recent years due to the advancement in technology to create more efficient modules and the increasing concern with our depleting fossil fuels along with its environmental impact.